Randomized study to assess the effectiveness of slow- and moderate-release polymer-based paclitaxel-eluting stents for coronary artery lesions. - Colombo, A; Drzewiecki, J; Banning, A; Grube, E; Hauptmann, K; Silber, S; Dudek, D; Fort, S; Schiele, F; Zmudka, K; Guagliumi, G; Russell, M (2003)
BACKGROUND: Early clinical studies demonstrated the feasibility of local paclitaxel delivery in reducing restenosis after treatment of de novo coronary lesions in small patient populations. METHODS AND RESULTS: We conducted a randomized, double-blind trial of 536 patients at 38 medical centers evaluating slow-release (SR) and moderate-release (MR) formulations of a polymer-based paclitaxel-eluting stent (TAXUS) for revascularization of single, primary lesions in native coronary arteries. Cohort I compared TAXUS-SR with control stents, and Cohort II compared TAXUS-MR with a second control group. The primary end point was 6-month percent in-stent net volume obstruction measured by intravascular ultrasound. Secondary end points were 6-month angiographic restenosis and 6- and 12-month incidence of major adverse cardiac events, a composite of cardiac death, myocardial infarction, and repeat revascularization. At 6 months, percent net volume obstruction within the stent was significantly lower for TAXUS stents (7.9% SR and 7.8% MR) than for respective controls (23.2% and 20.5%; P<0.0001 for both). This corresponded with a reduction in angiographic restenosis from 17.9% to 2.3% in the SR cohort (P<0.0001) and from 20.2% to 4.7% in the MR cohort (P=0.0002). The incidence of major adverse cardiac events at 12 months was significantly lower (P=0.0192) in the TAXUS-SR (10.9%) and TAXUS-MR (9.9%) groups than in controls (22.0% and 21.4%, respectively), predominantly because of a significant reduction in repeat revascularization of the target lesion in TAXUS-treated patients. CONCLUSIONS: Compared with a bare metal stent, paclitaxel-eluting stents reduced in-stent neointimal formation and restenosis and improved 12-month clinical outcome of patients with single de novo coronary lesions.